E-mail encryption framework for Malaysian public sector - Muhammad, Nur Atiqah (2016)
Securing confidential data shared through the electronic mail is depending on the current encryption method deployed by the E-mail service provider as well as the current procedures and regulation of the organization. Hence, the E-mail encryption framework is a fundamental factor in designing a secure E-mail service in the Malaysian Public Sector. Therefore, the purpose of this study is to develop the Email encryption framework for Malaysian Public Sector in order to secure the E-mail system. In this study, the qualitative study has been conducted in order to understand the criteria of the E-mail encryption framework for the Malaysian Public Sector. Thus, the descriptive design is conducted to discover the features E-mail encryption framework for Malaysian Public Sector from the E-mail administrator and related personnel. Therefore, in-depth interview with the semi-structured method of interview is used in this study. The E-mail encryption framework has been proposed which comprising of organizational, operational, technological, legal and ethical components. The proposed framework was evaluated to measure its effectiveness towards an existing e-mail system. Findings on the proposed e-mail encryption framework will benefit the Malaysian Public Sector in providing secure e-mail service thus deciding applicable security control. Finally, this study generally contributes to enhance the current secure e-mail system implementation in Malaysian public sector agencies.